Environmental modification via a quorum sensing molecule influences the social landscape of siderophore production. Issue 1852 (12th April 2017) - Popat, Roman; Harrison, Freya; da Silva, Ana C.; Easton, Scott A. S.; McNally, Luke; Williams, Paul; Diggle, Stephen P.
Abstract : Bacteria produce a wide variety of exoproducts that favourably modify their environment and increase their fitness. These are often termed 'public goods' because they are costly for individuals to produce and can be exploited by non-producers (cheats). The outcome of conflict over public goods is dependent upon the prevailing environment and the phenotype of the individuals in competition. Many bacterial species use quorum sensing (QS) signalling molecules to regulate the production of public goods. QS, therefore, determines the cooperative phenotype of individuals, and influences conflict over public goods. In addition to their regulatory functions, many QS molecules have additional properties that directly modify the prevailing environment. This leads to the possibility that QS molecules could influence conflict over public goods indirectly through non-signalling effects, and the impact of this on social competition has not previously been explored. The Pseudomonas aeruginosa QS signal molecule PQS is a powerful chelator of iron which can cause an iron starvation response. Here, we show that PQS stimulates a concentration-dependent increase in the cooperative production of iron scavenging siderophores, resulting in an increase in the relative fitness of non-producing siderophore cheats. This is likely due to an increased cost of siderophore output by producing cells and a concurrent increase in the shared benefits, which accrue to both producers and cheats. Although PQS can be a beneficial signalling molecule for P. aeruginosa, our data suggest that it can also render a siderophore-producing population vulnerable to competition from cheating strains. More generally, our results indicate that the production of one social trait can indirectly affect the costs and benefits of another social trait.